A Professional Decentralized Approach to Counselling (An Experiment in Counsellor Visibility) - Checkley, S. M. (Canadian Journal of Counselling and Psychotherapy, 2012)
A decentralized approach to counselling was initiated at theNorthern Alberta Institute of Technology following an examination ofthe effectiveness of our previous centralized approach. A counsellor wasstrategically located in the mainstream of student and staff movement.It was expected that this re-location would reduce instructor/counsellorbarriers to counselling. The intent, in such an approach, was to place counsellingin an "educational model" where the counsellor was located and integratedinto the scene of action as contrasted to the usual "medical model"where the student/staff must seek out the counsellor at some distant point.In the centralized approach students/staff often attach a stigma to counselling.Delay in seeking assistance results because counselling is perceivedas a last resort rather than as a resource. The presentation gives a description of the NAIT setting, an outline ofthe general objectives, the elements and rationale of the concept, evaluationof decentralization, a decentralization area and a summary.